A Finite Element Analysis on Sound Pressure and Pressure Drop on Diesel Generator Sets - Mudrikah, Syaza; Yahya, Musli Nizam (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Diesel generator sets are extensively utilized to produce energy and may also double as a backup power supply in the event of a power outage. However, it produces a noise that affects the peace and health of the environment. The aim of this study is to determine the sound pressure level and pressure drop of the diesel generator sets’ duct silencer by performing a CFD and Harmonic Response simulation by a finite element analysis software. The study is executed by simulating several parameters of the splitters of the silencers and comparing the results of the experiment to the theoretical results. The pressure drop over the discharge silencer and intake silencer, according to data received from ANSYS, is 14.2 Pa and 7.21 Pa, respectively whilst the sound pressure levels for the discharge silencer and intake silencer, according to the data in ANSYS, are 77.28 dB(A) and 73.6 dB(A), respectively. Other results for the comparison of silencers based on splitter dimension is also included. The results were found to be similar and the study is deemed successful, nonetheless, the design geometry must be improved to help reduce noise emissions and an advanced specifications of computers should be used for an effortless simulation analysis.